Nasiba THE PHENOMENON OF CONVERSION IN ENGLISH: THE PHENOMENON OF CONVERSION IN ENGLISH - Parmonova, Nasiba (Журнал иностранных языков и лингвистики, 2022)
The article analyzes conversion as a technique of producing new terms without adding any derivative elements when the basic form of the original and the basic derived words are homonymous, with the same morphological structure but belonging to distinct parts of speech. It also looks at conversion as a form of word construction rather than a structural relationship pattern. Both types – a noun and a verb – must be viewed as cases of patterned homonymy when studying synchronously; however, when studying diachronically, it is necessary to distinguish and treat the cases of conversion separately. It is stressed that determining which of the members was derived is difficult, and that the results of synchronic and diachronic analysis may differ. That is to say, what is meant by conversion in Modern English does not always and completely correspond to earlier stages of the language’s history. It is also argued that defining conversion as semantic derivation has substantial implications for the old, strictly categorial approach to polysemy.